Anti-obesity and antioxidant activities of selected medicinal plants and phytochemical profiling of bioactive compounds - Abdul Rahman, Hafeedza; Saari, Nazamid; Abas, Faridah; Ismail, Amin; Mumtaz, Muhammad Waseem; Abdul Hamid, Azizah (Taylor & Francis, 2017)
The present study describes the screening of eight herbs namely Cosmos caudatus, Pluchea indica, Lawsonia inermis, Carica papaya, Piper betle, Andrographis paniculata, Pereskia bleo, and Melicope lunu based on their anti-obesity and antioxidant activities. Out of all tested herbs, Cosmos caudatus demonstrated excellent anti-obesity and antioxidant potential with pancreatic lipase inhibitory effect (21.7 ± 1.3%) and DPPH radical scavenging activity (IC50 value of 31.98 ± 1.22 µg/mL). Cosmos caudatus was selected for further studies and extracting solvent composition with best anti-obesity and antioxidant potential was identified. Hundred percent Cosmos caudatus ethanolic extract was found to be the most effective and showed highest anti-obesity and antioxidant activities. Moreover, metabolite profiling of Cosmos caudatus extract was also carried out using UHPLC-MS/MS. The analysis depicted the presence of quercetin-3-rhamnoside, catechin, kaempherol, kaempherol glucoside, quercetin, quercetin-3-glucoside, quercetin-O-pentoside, quercetin-rhamnosyl galactoside, quinic acid, 1-caffeyolquinic acid, monogalloyl glucose, and procyanidin B1. Results revealed Cosmos caudatus as promising medicinal plant for the development of new functional food with prodigious applications in obesity.